Nilai Pendidikan Karakter Tawaduk dalam Buku Kisah-Kisah Kesabaran Para Ulama Karya Syekh Abdul Fattah Bin Muhammad - Sugianti Sugianti; Mintarga Eman Surya (UM Purwokerto Press, 2023)
Character education is an important part of education in Indonesia, the purpose of character education is to instill good character values in children. One of the important character values for children is the religious character which contains the value of a humble attitude which is important to grow in the child's soul. One of the media that can be a source of reference is a book that contains stories of pious people who exist today or in the past that can be learned from and are relevant in today's world of education. This research is a type of library research taken from a book by Sheikh Abdul Fattah bin Muhammad which was translated by Izzuddin Karimi with the title